RESERVOIR CHARACTERIZATION AND CO2 STORAGE CAPACITY ESTIMATION IN ARANG FORMATIONS IN THE SR FIELD, WEST NATUNA BASIN - Rizky Paramita, Valina
The Indonesian government keeps working on increasing oil and gas production to meet the country's demand for energy. On the other hand, efforts to reduce emissions towards Net Zero Emissions (NZE) in 2060 are also continuing. Utilization of emission reduction technologies such as Carbon Capture and Storage/Carbon Capture, Utilization and Storage (CCS/CCUS) can be a solution to this problem. In the application of the CCS method, the reservoir has a very important role as storage C02. One of the basins in Indonesia that is expected to have a good reservoir is the West Natuna Basin. The SR Field which is in the West Natuna Basin has started production activities since 2001 and is expected to carry out production until 2028. To reduce intensity of C02 emission the SR Field can be used as a storage place for C02 produced from the gas production process.